2012
DOI: 10.1042/bj20120386
|View full text |Cite
|
Sign up to set email alerts
|

miR-297 modulates multidrug resistance in human colorectal carcinoma by down-regulating MRP-2

Abstract: Colorectal carcinoma is a frequent cause of cancer-related death in men and women. miRNAs (microRNAs) are endogenous small non-coding RNAs that regulate gene expression negatively at the post-transcriptional level. In the present study we investigated the possible role of microRNAs in the development of MDR (multidrug resistance) in colorectal carcinoma cells. We analysed miRNA expression levels between MDR colorectal carcinoma cell line HCT116/L-OHP cells and their parent cell line HCT116 using a miRNA microa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(46 citation statements)
references
References 32 publications
1
45
0
Order By: Relevance
“…Interestingly, 16 miRNAs were diversely expressed in HCT116/L-OHP and HCT116 cells. Consistent with microarray data, quantitative RT-PCR analysis showed that miR-297 expression was downregulated in HCT116/L-OHP and HCT-8/VCR cells as compared to their parental cells (23).…”
Section: Mir-297 As Modulator Of Mrp2supporting
confidence: 66%
“…Interestingly, 16 miRNAs were diversely expressed in HCT116/L-OHP and HCT116 cells. Consistent with microarray data, quantitative RT-PCR analysis showed that miR-297 expression was downregulated in HCT116/L-OHP and HCT-8/VCR cells as compared to their parental cells (23).…”
Section: Mir-297 As Modulator Of Mrp2supporting
confidence: 66%
“…The other related studies almost focused on either 5-fluorouracil (Song et al, 2009;Boni et al, 2010;Valeri et al, 2010;Nishida et al, 2012) or oxaliplatin (Akao et al, 2011;Chai et al, 2011;Xu et al, 2012;Xu et al, 2013). Compared with the studies about one single agent, our work served the clinical practice better.…”
Section: Discussionmentioning
confidence: 88%
“…Recently, miRNAs have been suggested to play a key role in the development of MDR. 24 Through regulating gene expression, miRNAs can impact on different pathways associated with sensitivity or resistance to chemotherapeutic drugs in various tumors. [13][14][15][16][17] Several miRNAs, such as miR-106a, 25 miR-508-5p 26 and miRNA-19a/b 27 have been reported to play a role in the development of MDR in GC.…”
Section: Discussionmentioning
confidence: 99%